2002
DOI: 10.1097/01.lab.0000017170.26718.89
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Localized Amyloidosis Associated with Lactoferrin in the Cornea

Abstract: SUMMARY:We report a novel localized amyloidosis associated with lactoferrin. To elucidate the precursor protein of corneal amyloidosis associated with trichiasis, we analyzed amyloid deposits from three patients by histopathology and biochemistry. Amyloid deposits showed immunoreactivity, confirmed by electron microscopy, for only anti-human lactoferrin antibody. Electrophoresis of amyloid fibrils revealed lactoferrin with and without sugar chains; N-terminal sequence analysis revealed full-length lactoferrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 41 publications
2
24
0
1
Order By: Relevance
“…Lactoferrin, a major, 78.2-kDa component of tears, has attracted attention because it was found in GDLD amyloid deposits 24 and because lactoferrin fragments can form amyloid fibrils in vitro. 25,26 Although the source of lactoferrin in the amyloid deposits remains to be determined, it may originate from the tear film and penetrate disturbed cell junctions. Alternatively, its presence may be attributable to the overexpression of the lactoferrin gene in epithelial cells although a link between the lactoferrin-and M1S1 gene has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin, a major, 78.2-kDa component of tears, has attracted attention because it was found in GDLD amyloid deposits 24 and because lactoferrin fragments can form amyloid fibrils in vitro. 25,26 Although the source of lactoferrin in the amyloid deposits remains to be determined, it may originate from the tear film and penetrate disturbed cell junctions. Alternatively, its presence may be attributable to the overexpression of the lactoferrin gene in epithelial cells although a link between the lactoferrin-and M1S1 gene has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the precursor protein in corneal amyloidosis associated with trichiasis is lactoferrin. 16 Although all of the patients in the previous study were heterozygotes for lactoferrin Glu561Asp gene, no statistical significance was observed when compared with that of the polymorphism in healthy control subjects. Although trichiasis itself is not so uncommon, the incidence of corneal amyloidosis is quite low.…”
mentioning
confidence: 83%
“…Analyses for lactoferrin Glu561Asp were performed via PCR-IMRA as described. 16 When allele for lactoferrin Glu561Asp only exists, the digestion bands (158 bp and 28 bp) are observed.…”
Section: Figurementioning
confidence: 99%
“…Lf gene analysis in the 3 patients revealed a Glu561Asp mutation, and a compound heterozygote of Ala11Thr and Glu561Asp mutations in 1 patient. Heterozygotic Glu561Asp mutation was found in 44.8% of healthy Japanese volunteers, suggesting that the mutation may not be an essential mutation for amyloid formation (p=0.104), and that Lf was this precursor protein [463].…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…Ando et al [463] reported that in three patients with corneal amyloidosis electrophoresis of amyloid fibrils revealed Lf with and without sugar chains, and N-terminal sequence analysis demonstrated full-length Lf and a truncated tripeptide of N-terminal amino acids, Gly-Arg-Arg. Carboxymethylated wild-type Lf formed amyloid fibrils in vitro.…”
Section: T Gondii Infectionmentioning
confidence: 99%